Uterine hydatidosis: casuistry is possible - A. L. Tikhomirov; V. V. Kazenashev; A. A. Dubinin; R. R. Sadikova; M. V. Maminova; J. S. Globa; A. V. Bukharov (IRBIS LLC, 2024)
Introduction. Hydatidosis is a severe parasitic disease caused by tapeworm Echinococcus granulosus widely spread in some endemic areas all over the world that primarily targets liver, lung, bones, muscles well as pelvis in casuistic cases. Due to the lack of pathognomonic signs as well as low prevalence rate of hydatid cysts in such anatomic sites, a differential diagnosis for relevant gynecological pathologies may be substantially complicated. Compared with common gynecological disease such as uterine fibroids, ovarian cyst and malignancies uterine hydatidosis may be identified only in 0.16 % cases.Aim: to present a clinical case of uterine hydatid cyst in order to optimize algorithms for differential diagnosis of primary pelvic echinococcosis and gynecological pathology, which is necessary for successfully conducted timely surgical treatment.Clinical case. In 2023, patient K. complained of dysuric phenomena and a feeling of heaviness in the pelvic area. Based on the anamnesis, clinical picture, laboratory and instrumental research methods, it was decided to perform surgical treatment. The patient underwent laparoscopic hysterectomy and removal of ¾ hydatid cyst. The obtained material was used for histological examination to verify the diagnosis.Results. Differential diagnosis of uterine echinococcosis is most often carried out with cystic or dysembryogenetic tumors, purulent or tuberculous abscesses, ovarian cysts, ovarian tumors, and uterine fibroids. Features of the MR picture, such as a thick compacted wall, the lack of internal septa, parietal and papillary outgrowths, as well as a solid component, allowed to suspect parasitic genesis of the neoplasm.Conclusion. While treating patients with cystic neoplasms of the pelvic area referred from endemic areas, echinococcosis should be included in the list of differential diagnostic searches.